Analisis model pembelajaran kitab klasik di pondok pesantren Nurul Junaidiyah Lauwo - Aswaluddin; Haris Kulle; Fauziah Zainuddin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims: 1) To find out the analysis of the classical book learning model at the Nurul Junaidiyah Lauwo Islamic Boarding School, Burau District, East Luwu Regency. 2) To describe the steps of the classical book learning model developed at the Nurul Junaidiyah Lauwo Islamic Boarding School, Burau District, East Luwu Regency. 3) To find out the obstacles and solutions from the analysis of the classic book learning model at the Nurul Junaidiyah Lauwo Islamic Boarding School, Burau District, East Luwu Regency. This type of research is descriptive qualitative research. This research is intended to raise the facts, circumstances, variables, and phenomena that occur. The research approach is sociological psychological pedagogy. The data sources used are primary data and secondary data. Data collection techniques and instruments are observation, interviews and documentation. The results of this study indicate that, 1) The classic book learning model at the Nurul Junaidiyah Islamic Boarding School Lauwo, Burau District, East Luwu Regency, namely the Classical Book learning model is for achieving systematic learning mastery. Competency standards or basic competencies to be achieved in the early stages are the strengthening of basic knowledge, namely nahwu and sharaf sciences. Furthermore, students are expected to be ready to study Arabic books without vowels. The main material studied is fardhu ain sciences, namely monotheism, fiqh and morals. 2) The steps for the classical book learning model were developed at the Nurul Junaidiyah Lauwo Islamic Boarding School, Burau District, East Luwu Regency, namely planning, implementing learning. 3) Constraints and solutions from the analysis model of learning classic books at the Nurul Junaidiyah Lauwo Islamic Boarding School, Burau District, East Luwu Regency. The obstacles are the lack of regeneration of staff, lack of pesantren funds, pesantren development efforts, not having a standardized curriculum and lack of facilities and infrastructure. While the solution is to increase the cadre of teaching staff, attract alumni and have an operational business.